Kontekstualisasi Teologi sebagai Basis Gerakan Ekologi - Khitam, Husnul (IAIN Surakarta, 2016)
Pesantren as an indigenous Islamic based education institution in Indonesia has been always reflecting its social action by the religious values, including to their ecological activities. This research attempts to explore the role of pesantren on community empowerment, especially on how theologically and sociologically the movement created and perceived through society. The main question of this research is on how pesantren interpret various environmental problems through the eco-theological perspectives. This research represented by two pesantrens, modern and traditional. From theological landscape, they used Alquran as the primary source for the ecological movement and contextualizing it into the internal pesantren communities and to their surrounding communities. Pesantren Al-Amin, as the traditional one using transcendent relations as the basic theological framework, term like Kutub Alaulia and the conception of almsgiving used as its central point. Meanwhile, pesantren Daarul Ulum Lido put the basic values of the ecological movement into conception of Fiqh Albiah and conception of Caliphs to build student amorousness to environment by the narrative of sustainability and the future human generation.KeywordsPesantren, Ecology, Theology, and Contextualization